Women or children? Intra-household redistribution under gender-asymmetric altruism - Indraneel Dasgupta (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
In developing societies, social norms typically ascribe differential weights to paternal, maternal and communal (or state) contributions to children's expenses. Individuals internalize these valuations. I examine a Cournot model of voluntary contribution to children's goods in a twoadult household, where both spouses may have marginal rates of substitution across paternal, maternal and communal contributions that differ from unity. I show that a conflict may exist between the interests of parents and those of children. Depending on the marginal rate of substitution between paternal and maternal contributions, a lump-sum redistribution from fathers to mothers may make children better off, but both parents worse off, or vice versa. Additional public contribution funded by a lump-sum tax on either parent may make children better off, but at the cost of both parents. Thus, proposals to redistribute income from fathers to mothers need to take into account socially valorized gendered asymmetries in parental roles. Furthermore, there may exist a conflict, instead of congruence, between women and their children.
Keywords: H23; H31; I38; J16; 330; Intra-household distribution; social norms; domestic public good; redistribution; Haushaltseinkommen; Soziale Norm; Einkommensumverteilung; Geschlecht; Haushaltsökonomik; Theorie